Professional Writing in Kinesiology and Sports Medicine - Knoblauch, Mark (SLACK, Incorporated, 2018)
Publication of a research article can be a defining moment in a researcher's career. However, the steps involved in turning an initial research question into a published article can be a long and arduous journey. To aid in this process, Professional Writing in Kinesiology and Sports Medicine was developed to serve as a comprehensive writing guide for research professionals and students who are looking to improve their academic writing skills.